Employees pro-enviromental behavior of hotels in Tangerang and Jakarta during pandemic Covid-19 - Yohana F. Cahya Palupi Meilani; Rudy Pramono (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The objective of this research is determining effect of variables environmental leadership to pro enviromental behavior with top management commitment as moderating variable of hotels in Tangerang and Jakarta during pandemic Covid-19. This study applies a quantitative research using a sample size of 171 respondents who are employees of five stars hotels in Jakarta and Tangerang. The data was gathered through the use of a questionnaire which is then processed and analysed using the Partial Least Square to show whether hypotheses offered in this research is accepted or rejected. Results achieved in this research shows a positive influence of top management commitment, active environmental leadership, and motivation towards employees’ pro enviromental behavior, however passive environmental leadership does not appear to negatively impact employees’ pro enviromental behavior. The moderation of top management commitment to direct managers is also rejected. The contribution of this research is to provide support to future research and to any party who would like to seek some understanding about the relation between the rising concern of environmental behaviours of employees and the organization. The results and data gathered in this research could contribute to a firm’s management to maintain a healthy relationship with employees, and to shift strategies to align their organizational strategy with employees’ pro enviromental behavior.